A Multistate Investigation of Serious Adverse Events, including Deaths, following Ceftriaxone Injections, September 2024–August 2025 - Rebecca Pierce; Radhika Agarwal; Dumbani Kayira; Maribeth C Lovegrove; Nimalie D Stone; Kelly M Hatfield; Jennifer Lind Lyles; Melissa Morrison; Wes Stubblefield; Sherri L Davidson; Karen Landers; Scott Harris; et al. (Clinical Infectious Diseases, 2026)
Abstract Background Reports of ceftriaxone serious adverse events (SAEs), including deaths, from multiple jurisdictions during December 2024–January 2025 prompted a nationwide investigation to evaluate product safety, characterize SAEs, and assess for changes in baseline adverse event occurrence via national databases. Methods In February 2025, CDC issued a national call for cases, defined as SAEs involving death or CPR within six hours of ceftriaxone injection, not otherwise explained and occurring in non-ICU settings during September 2024-August 2025. Epidemiologic and clinical data were collected by health departments and reported to CDC. Laboratory testing of ceftriaxone and lidocaine diluent was performed at FDA. Temporal trends in adverse events (2016–2019 vs 2020–2024) were assessed via Medicare claims and National Electronic Injury Surveillance System-Cooperative Adverse Drug Event Surveillance System analyses. Results Among 31 cases identified from 27 healthcare facilities (65% outpatient) across 18 states during September 2024–August 2025, all involving death or CPR, 12 (39%) persons died, 23 (74%) had anaphylaxis-type presentations (65% without skin/mucosal involvement), 21 (68%) had previous ceftriaxone exposure, and 24 (77%) had cardiac comorbidities. Median age was 67 years (IQR: 60–81). Antihypertensive use was common (n=19/28, 68%). Product testing revealed no evidence of tampering, adulteration, endotoxin, or purity/potency issues. National adverse event trends were stable across 2016–2019 and 2020–2024. Conclusions SAEs, including deaths, can occur after ceftriaxone receipt. Product testing and trend analyses did not identify evidence of a new safety issue. This investigation highlights the need for ongoing vigilance for ceftriaxone SAEs and reporting to FDA MedWatch.